Flexible pressure sensor, conductive ink and preparation method thereof

By using chemically modified polyester resin and conductive filler to prepare conductive inks and applying them to the preparation of flexible pressure sensors, the problems of low sensitivity and easy saturation of flexible pressure sensors in the prior art are solved, and high sensitivity and wideness are achieved Flexible pressure sensor with force response range and good piezoresistive stability.

CN119463586APending Publication Date: 2025-02-18KUNSHAN SHUIMU YUANKUN TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411631464.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing flexible pressure sensors have low sensitivity and are prone to saturation of force resistance, so they cannot respond accurately and quickly to pressure changes in complex environments.

Method used

Conductive inks are prepared using chemically modified saturated polyester resin and chemically modified conductive fillers, and a screen printed piezoresistive sensing layer of flexible pressure sensors is made from conductive inks. The conductive ink improves the conductivity and dispersion through the synergistic effect of quaternary ammonium modified nanocellulose and conductive filler.

Benefits of technology

It improves the sensitivity and range of the flexible pressure sensor, enhances the piezoresistive stability and service life, and makes it highly responsive in small pressure to large pressure ranges, and is suitable for expansion force testing in the field of energy storage batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463586A_ABST
    Figure CN119463586A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of conductive ink and sensor production, in particular to a flexible pressure sensor, conductive ink and a preparation method thereof.The preparation method comprises the steps that S1, a modified polyester resin composition is prepared; s2, quaternary ammonium salt modified nanocellulose and a conductive filler are adopted as raw materials to prepare a modified conductive filler; s3, respectively weighing the modified polyester resin composition, the modified conductive filler, a solvent and an auxiliary agent in proportion, adding the materials into a reaction kettle, dispersing, and stirring at a high speed to obtain conductive ink coarse slurry; s4, grinding the conductive ink coarse slurry, adjusting the distance between roll shafts to enable the fineness of the slurry not to exceed 20 microns, filtering and discharging to obtain conductive ink powder; s5, the viscosity is adjusted to be in the range of 5000 cps to 12000 cps, and the conductive ink is obtained. Through the synergistic effect of the components in the conductive ink, the flexible pressure sensor made of the conductive ink has high sensitivity and a wide enough force response range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive ink and sensor production, and in particular to a flexible pressure sensor, conductive ink and a preparation method thereof. Background Art

[0002] Flexible electronics is an emerging electronic technology that makes electronic devices made of organic / inorganic materials on flexible / ductile substrates. With its unique flexibility / ductility and efficient and low-cost manufacturing process, it has broad application prospects in the fields of information, energy, medical care, and national defense. At present, with the increasing requirements for the portability, comfort and flexibility of electronic products, flexible electronic technology is also constantly developing and progressing; among them, flexible pressure sensors, as a flexible electronic device that can sense pressure changes, are composed of conductive materials, flexible materials, etc., can be bent, stretched and twisted, and can adapt to stress changes of different shapes and surfaces, and have broad application prospects. However, despite the excellent performance of flexible pressure sensors in flexibility and stability, they still face some technical challenges in practical applications; for example, how to improve the sensitivity while improving key parameters such as range and response time is still a difficult problem; therefore, how to improve the sensitivity of the sensor so that it can accurately and quickly respond to pressure changes in various complex environments is still the focus and difficulty of current research.

[0003] In the field of energy storage, flexible pressure sensors can be used to test battery expansion force. Currently, common battery pressure expansion force detection devices generally include thin film pressure sensors and their matching collectors. Among them, thin film pressure sensors are usually array-distributed multi-sensing point structures. According to the size and area of ​​the battery pack and comprehensive consideration of cost, pressure sensing points of different sizes and array densities are designed. When testing the pressure expansion force of the battery, the pressure sensor is required to have a sufficiently wide range and sensitivity, so the performance requirements of the flexible pressure sensor are relatively high. Commonly used thin film pressure sensors are composed of upper and lower electrode layers, upper and lower sensing layers, isolation lamination layers and packaging layers. Among them, the sensing layer basically determines the sensitivity and range of the sensor itself. At present, most flexible pressure sensors improve their sensitivity by designing microstructures in the sensing material, but because the deformation of the microstructure is easily saturated under greater pressure, its sensitivity and overall sensing performance decrease, and a sufficiently wide range and sensitivity cannot be obtained. Therefore, in order to improve the sensitivity and range of the sensor, it is necessary to further study new materials. For example, exploring a nanomaterial with higher conductivity and flexibility or developing a new polymer material with a special sensitive mechanism are effective ways to improve the sensitivity and range of the sensor.

[0004] The present application provides a flexible pressure sensor, conductive ink and a preparation method thereof, so as to solve the problems of the existing flexible pressure sensors in the prior art, such as low sensitivity and easy saturation of force resistance. Summary of the invention

[0005] The purpose of the present invention is to provide a flexible pressure sensor, conductive ink and a preparation method thereof, so as to solve the problems of the existing flexible pressure sensors in the prior art, such as low sensitivity and easy saturation of force resistance.

[0006] The technical solution of the present invention is: a method for preparing a conductive ink, comprising the following steps:

[0007] S1. Prepare a modified polyester resin composition for standby use; wherein the preparation steps of the modified polyester resin composition include:

[0008] a. Weigh 100 parts of saturated polyester resin, 10-40 parts of xylene, and 10-30 parts of diisocyanate monomer respectively by mass, and add the weighed saturated polyester resin, xylene, and diisocyanate monomer into a reactor in sequence under nitrogen protection, then raise the temperature in the reactor from room temperature to 50-80° C., stir, so that the terminal hydroxyl group on the saturated polyester resin reacts with the isocyanate monomer, and after reacting for 0.5-1h, a polyester with an active group at the end is generated;

[0009] b. Weigh 10-30 parts of an acrylic monomer with a hydroxyl group and 0.05-0.2 parts of dibutyltin diacetate respectively by mass, and add the weighed acrylic monomer with a hydroxyl group and dibutyltin diacetate to a reaction kettle in sequence, continue stirring, so that the polyester with an active group at the end and the acrylic ester monomer with a hydroxyl group undergo a cross-linking reaction, react for 1-4 hours, and then cool down to obtain a modified polyester resin composition;

[0010] S2, using quaternary ammonium salt modified nanocellulose and conductive filler as raw materials to prepare modified conductive filler for standby use;

[0011] S3, weighing the modified polyester resin composition prepared in step S1, the modified conductive filler prepared in step S2, the solvent, and the additives respectively according to proportion, and adding the weighed modified polyester resin composition, modified conductive filler, solvent, and additives into a reaction kettle, dispersing for 0.5-1h, and then stirring at a high speed for 1h-4h to obtain a conductive ink coarse slurry;

[0012] S4, transferring the obtained conductive ink coarse slurry to a grinder for grinding, adjusting the roller spacing so that the slurry fineness does not exceed 20 μm, filtering the material to obtain conductive ink powder;

[0013] S5. The viscosity of the obtained conductive ink powder is adjusted to within the range of 5000 cps-12000 cps, and the powder is fully stirred and mixed to obtain conductive ink.

[0014] Preferably, the diisocyanate monomer is any one or a combination of hexamethylene diisocyanate, isophorone diisocyanate, p-phenylene diisocyanate, and 1,4-cyclohexane diisocyanate;

[0015] The acrylic monomer with hydroxyl group is any one of hydroxyethyl methacrylate, hexanediol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, and triethylene glycol dimethacrylate, or a combination of several of them.

[0016] Preferably, the step of preparing the modified conductive filler comprises:

[0017] i. Prepare a quaternary ammonium salt-modified nanocellulose dispersion with a mass percentage of 0.3%-3%;

[0018] ii. Weigh the quaternary ammonium salt-modified nanocellulose dispersion and the conductive filler prepared in step i respectively according to proportion, and add the conductive filler to the quaternary ammonium salt-modified nanocellulose dispersion under stirring. Then, raise the temperature of the quaternary ammonium salt-modified nanocellulose dispersion from room temperature to 60° C.-90° C. to react. After reacting for 1 h-5 h, vacuum filtration, drying and grinding are performed to obtain a modified conductive filler.

[0019] Preferably, in the step ii, calculated by weight, the quaternary ammonium salt-modified nanocellulose dispersion is 100 parts, and the conductive filler is 30 parts.

[0020] Preferably, the conductive filler comprises carbon black and copper powder, and the weight ratio of carbon black to copper powder is 99:1-70:30; the average particle size of the carbon black and the copper powder is 0.5-100 μm.

[0021] Preferably, the average particle size of the modified conductive filler is 0.3 μm-20 μm.

[0022] Preferably, in step S3, the modified polyester resin composition is 10-30 parts, the modified conductive filler is 3-30 parts, the solvent is 5-40 parts, and the auxiliary agent is 0.5-3 parts, calculated by weight.

[0023] The solvent is any one or more of DMF, NMP, cyclohexanone, dichloromethane and xylene;

[0024] The auxiliary agent is any one or more combinations of leveling agents and defoaming agents.

[0025] The present invention also provides a conductive ink, which is prepared by the above-mentioned preparation method.

[0026] The present invention also provides a flexible pressure sensor, comprising two silk-screened electrode layers, two double-sided adhesive layers, and two silk-screened piezoresistive sensing layers; one silk-screened electrode layer and one silk-screened piezoresistive sensing layer are symmetrically bonded on both sides of each of the double-sided adhesive layers; the two silk-screened piezoresistive sensing layers are close to each other, so that the two double-sided adhesive layers are stacked up and down;

[0027] The silk-screen piezoresistive sensing layer is prepared by using the above-mentioned conductive ink as silk-screen raw material.

[0028] Compared with the prior art, the advantages of the present invention are:

[0029] (1) The present invention provides a flexible pressure sensor, conductive ink and a preparation method thereof. The conductive ink is prepared using raw materials such as a chemically modified saturated polyester resin and a chemically modified conductive filler. Through the synergistic effect of the various components in the conductive ink, not only can the flexible pressure sensor made using the conductive ink have higher sensitivity and a sufficiently wide force response range, but the flexible pressure sensor can also have better piezoresistive stability and a longer service life. The problems of the existing flexible pressure sensors in the prior art, such as low sensitivity and easy saturation of force resistance, are solved.

[0030] (2) The present invention provides a flexible pressure sensor, conductive ink and a preparation method thereof. In the process of preparing the conductive ink, the terminal hydroxyl group of a saturated polyester resin is firstly bonded to one of the isocyanate groups on a diisocyanate monomer through a chemical bond to form a polyester polymer having an active group at the end; the polyester polymer having an active group at the end is then further grafted and cross-linked with an acrylate monomer having a hydroxyl group to form a macromolecule with a body structure, thereby modifying the saturated polyester resin. This not only helps to evenly disperse the conductive filler in the polymer carrier, but also improves the long-term aging resistance of the conductive ink system.

[0031] (3) The present invention provides a flexible pressure sensor, conductive ink and a preparation method thereof. In the process of preparing the conductive ink, nanocellulose modified with quaternary ammonium salt is used to modify and disperse the conductive filler, which can further improve the subsequent dispersion ability of the conductive filler in the conductive ink system; the conductive filler can be arranged closely when filled between the modified polyester resin composition to form an efficient conductive channel; and the screen-printed piezoresistive sensing layer made by using the conductive ink prepared by the present invention as the screen-printing raw material has high sensitivity at the pressure sensing points within a wide pressure range and a long service life; the prepared flexible pressure sensor can be applied to the expansion force test in the field of energy storage batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0033] Figure 1 This is a schematic diagram of the structure of a flexible pressure sensor prepared in an embodiment of the present invention;

[0034] Figure 2 This is a physical picture of a 5*6 array flexible pressure sensor prepared in an embodiment of the present invention;

[0035] Among them: 1. Silk-screen electrode layer; 2. Double-sided adhesive layer; 3. Silk-screen piezoresistive sensing layer. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with specific embodiments:

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0038] Example 1

[0039] S1, preparing a modified polyester resin composition for standby use; wherein the preparation steps of the modified polyester resin composition include:

[0040] a. Weigh 100 parts of saturated polyester resin, 20 parts of xylene, and 30 parts of isophorone diisocyanate respectively by mass, and add the weighed saturated polyester resin, xylene, and isophorone diisocyanate into a reactor in sequence under nitrogen protection, then raise the temperature in the reactor from room temperature to 80° C., stir, so that the terminal hydroxyl group on the saturated polyester resin reacts with one of the isocyanate groups on the isophorone diisocyanate monomer, and after reacting for 1 hour, a polyester with an active group at the end is generated;

[0041] b. Weigh 30 parts of hydroxyethyl methacrylate monomer with hydroxyl group and 0.05 parts of dibutyltin diacetate respectively by mass, and add the weighed hydroxyethyl methacrylate monomer with hydroxyl group and dibutyltin diacetate to the above-mentioned reaction kettle in sequence, continue stirring, so that the polyester with active groups at the end and the hydroxyethyl methacrylate monomer with hydroxyl group undergo cross-linking reaction, and cool down after reacting for 4 hours to obtain a modified polyester resin composition. Dibutyltin diacetate is used as a catalyst in the reaction system, and other catalysts with the same catalytic function can also be used to replace the dibutyltin diacetate in this embodiment; the obtained modified polyester resin composition includes modified polyesters with macromolecular structures of different reaction degrees and unreacted monomers. In other embodiments, calculated by weight, the various raw materials weighed in step a may be 100 parts of saturated polyester resin, 10-40 parts of xylene, and 10-30 parts of isocyanate monomer; the various raw materials weighed in step b may be 10-30 parts of acrylic monomer with hydroxyl group, and 0.05-0.2 parts of dibutyltin diacetate; at the same time, the temperature in the reactor may be raised from room temperature to 50-80°C.

[0042] In the present invention, during the reaction of the terminal hydroxyl group of the saturated polyester resin with the isocyanate group on the diisocyanate, since the saturated polyester resin has a larger structure and a larger spatial position, after one of the isocyanate groups on the diisocyanate reacts with the terminal hydroxyl group of the saturated polyester resin, it is difficult for the other isocyanate group to react with the terminal hydroxyl group of the saturated polyester resin. Therefore, the reaction product of the terminal hydroxyl group of the saturated polyester resin and the diisocyanate is mainly a polyester with an active group at the end, and the reaction formula of the reaction is: NCO–R–NCO+HO–R′=NCO–R–NH–COOR′; wherein HOR′ is the saturated polyester resin and NCO–R–NCO is the diisocyanate.

[0043] S2. Using quaternary ammonium salt-modified nanocellulose and conductive filler as raw materials, preparing modified conductive filler for standby use; wherein the specific process steps for preparing the modified conductive filler are as follows:

[0044] i. Weigh an appropriate amount of quaternary ammonium salt-modified nanocellulose dispersion and prepare it into a quaternary ammonium salt-modified nanocellulose dispersion with a mass percentage of 2%;

[0045] ii. Calculated by mass, 100 parts of the quaternary ammonium salt-modified nanocellulose dispersion prepared in step i and 30 parts of a conductive filler are weighed respectively, and the weighed conductive filler is added to the quaternary ammonium salt-modified nanocellulose dispersion under stirring. Thereafter, the temperature of the quaternary ammonium salt-modified nanocellulose dispersion is raised from room temperature to 90°C, and after reacting for 3 hours, vacuum filtration, drying and grinding are performed to obtain a modified conductive filler with an average particle size of 10 μm; wherein the conductive filler comprises carbon black and copper powder, and in the conductive filler, the weight ratio of carbon black to copper powder is 70:30; and the average particle sizes of carbon black and copper powder are both 30 μm. In other embodiments, in the prepared quaternary ammonium salt modified nanocellulose dispersion, the mass percentage of quaternary ammonium salt modified nanocellulose can be 0.3%-3%; the weight ratio of the conductive filler carbon black to the copper powder can be 99:1-70:30; and the average particle size of the carbon black and the copper powder are both in the range of 0.5-100 μm; the average particle size of the modified conductive filler can also be 0.3μ-20μm.

[0046] S3. Weigh 30 parts of the modified polyester resin composition prepared in step S1, 20 parts of the modified conductive filler prepared in step S2, 30 parts of DMF, and 2 parts of leveling agent, respectively, by mass, and add the weighed modified polyester resin composition, modified conductive filler, DMF and leveling agent into a reactor, use an agitator and disperse them at a speed of 300 r / min. After dispersing for 0.5-1h, stir at a speed of 3000 r / min for 2h to obtain a coarse slurry of conductive ink.

[0047] S4. The obtained conductive ink coarse slurry is transferred to a grinder for grinding, the roller spacing is adjusted so that the slurry fineness does not exceed 20 um, and the material is filtered to obtain conductive ink powder.

[0048] S5. Adjust the viscosity of the obtained conductive ink powder to 8000cps, stir it thoroughly, and mix it evenly to obtain conductive ink. In other embodiments, the weight parts of various materials weighed in step S3 can be 10-30 parts of the modified polyester resin composition, 3-30 parts of the modified conductive filler, 5-40 parts of the solvent, and 0.5-3 parts of the auxiliary agent. At the same time, the solvent can also be any one or more combinations of DMF, NMP, cyclohexanone, dichloromethane, xylene, etc.; the auxiliary agent can be any one or more combinations of leveling agents, defoaming agents, etc.; in addition, the viscosity of the conductive ink powder can also be in the range of 5000cps-12000cps.

[0049] The conductive ink prepared as above can be used as a screen printing material to prepare a screen-printed piezoresistive sensing layer, that is, the conductive ink is screen-printed at the sensing point position on the sensing layer, and then the sensing layer is cured at 130°C for 30 minutes to obtain a screen-printed piezoresistive sensing layer; and the prepared screen-printed piezoresistive sensing layer is used to make a flexible pressure sensor. Figure 1 As shown, the flexible pressure sensor includes two silk screen electrode layers 1, two double-sided adhesive layers 2, and two silk screen piezoresistive sensing layers 3; a silk screen electrode layer 1 and a silk screen piezoresistive sensing layer 3 are symmetrically bonded to both sides of each double-sided adhesive layer 2; then the two silk screen piezoresistive sensing layers 3 are placed close to each other, so that the two double-sided adhesive layers 2 are stacked up and down to obtain a flexible pressure sensor. In other embodiments, in the process of preparing the silk screen piezoresistive sensing layer, the curing temperature can be in the range of 130-150°C; the curing time is in the range of 20-60min.

[0050] The conductive ink prepared above and the method for making a flexible pressure sensor are used to make a 5*6 array flexible pressure sensor, such as Figure 2 As shown, the area of ​​each sensing point of the 5*6 array flexible pressure sensor is 1cm 2 , the spacing between the sensing points is 8 mm; then, the performance of the 5*6 array flexible pressure sensor is tested.

[0051] The flexible pressure sensor manufactured in this embodiment has high sensitivity to the expansion force of the battery pack under conditions ranging from small pressure to large pressure, and can detect and warn the expansion force between energy storage battery packs.

[0052] Example 2

[0053] S1. Prepare a modified polyester resin composition for standby use; first, weigh 100 parts of a saturated polyester resin, 10 parts of xylene and 10 parts of 1,4-cyclohexane diisocyanate by mass, and add the weighed saturated polyester resin, xylene and 1,4-cyclohexane diisocyanate to a reactor in sequence under nitrogen protection, then raise the temperature in the reactor from room temperature to 60°C, stir, so that the terminal hydroxyl group on the saturated polyester resin and one of the isocyanates on the 1,4-cyclohexane diisocyanate monomer are bonded to each other. The acid radical group reacts, and after the reaction is 0.5, a polyester with an active group at the end is generated; then, 30 parts of trimethylolpropane triacrylate and 0.1 parts of dibutyltin diacetate are weighed respectively by mass, and the weighed trimethylolpropane triacrylate and dibutyltin diacetate are added to the above-mentioned reaction kettle in sequence, and stirring is continued to allow the polyester with an active group at the end to undergo a cross-linking reaction with the trimethylolpropane triacrylate monomer with a hydroxyl group, and the temperature is lowered after the reaction for 1 hour to obtain a modified polyester resin composition.

[0054] S2, using quaternary ammonium salt modified nanocellulose and conductive filler as raw materials, preparing modified conductive filler for standby use; first, preparing a dispersion of quaternary ammonium salt modified nanocellulose with a mass percentage of 3%; secondly, weighing 100 parts of the prepared quaternary ammonium salt modified nanocellulose dispersion and 30 parts of conductive filler, and adding the weighed conductive filler to the quaternary ammonium salt modified nanocellulose dispersion under stirring; then, raising the temperature of the quaternary ammonium salt modified nanocellulose dispersion from room temperature to 60°C, reacting for 3 hours, vacuum filtering, drying, and grinding to obtain a modified conductive filler with an average particle size of 10μm. Among them, the components of the conductive filler are carbon black and copper powder, and the weight ratio of carbon black to copper powder is 99:1, and the average particle size of carbon black and copper powder is 10μm.

[0055] S3. Weigh 20 parts by mass of the modified polyester resin composition prepared in step S1, 30 parts by mass of the modified conductive filler prepared in step S2, 5 parts by mass of cyclohexanone, and 1 part by mass of the leveling agent. Add the weighed modified polyester resin composition, modified conductive filler, cyclohexanone and leveling agent into a reactor, and disperse them using an agitator at a speed of 500 r / min. After dispersing for 3 hours, stir at a speed of 6000 r / min for 1 hour to obtain a coarse slurry of conductive ink.

[0056] S4. The obtained conductive ink coarse slurry is transferred to a grinder for grinding, and the roller spacing is adjusted to make the slurry fineness reach less than 20 um, and the material is filtered to obtain conductive ink powder.

[0057] S5. Adjust the viscosity of the obtained conductive ink powder to 5000 cps, stir it thoroughly, and mix it evenly to obtain conductive ink.

[0058] The prepared conductive ink was used as a silk-screen raw material, and the silk-screen piezoresistive sensing layer and a 5*6 array flexible pressure sensor were prepared in sequence by the same preparation method as in Example 1; and the area of ​​each sensing point on the prepared 5*6 array flexible pressure sensor was 1 cm 2 , the spacing between the sensing points is 8mm.

[0059] Example 3

[0060] S1. Prepare a modified polyester resin composition for standby use; first, weigh 100 parts of a saturated polyester resin, 40 parts of xylene and 20 parts of hexamethylene diisocyanate by mass, and add the weighed saturated polyester resin, xylene and hexamethylene diisocyanate to a reactor in sequence under nitrogen protection, then raise the temperature in the reactor from room temperature to 60°C, stir, so that the terminal hydroxyl group on the saturated polyester resin reacts with one of the isocyanate groups on the hexamethylene diisocyanate monomer, and after 0.5 of the reaction, a polyester with an active group at the end is generated; then, weigh 20 parts of triethylene glycol dimethacrylate and 0.2 parts of dibutyltin diacetate by mass, and add the weighed triethylene glycol dimethacrylate and dibutyltin diacetate to the above reactor in sequence, continue stirring, so that the polyester with an active group at the end reacts with the triethylene glycol dimethacrylate monomer with a hydroxyl group, and cool after reacting for 1 hour to obtain a modified polyester resin composition.

[0061] S2, using quaternary ammonium salt modified nanocellulose and conductive filler as raw materials, preparing modified conductive filler for standby use; first, preparing a dispersion of quaternary ammonium salt modified nanocellulose with a mass percentage of 0.3%; secondly, weighing 100 parts of the prepared quaternary ammonium salt modified nanocellulose dispersion and 30 parts of conductive filler, and adding the weighed conductive filler to the quaternary ammonium salt modified nanocellulose dispersion under stirring; then, raising the temperature of the quaternary ammonium salt modified nanocellulose dispersion from room temperature to 80°C, reacting for 5 hours, vacuum filtration, drying, and grinding to obtain a modified conductive filler with an average particle size of 0.3μm. Among them, the components of the conductive filler are carbon black and copper powder, and the weight ratio of carbon black to copper powder is 80:20, and the average particle size of carbon black and copper powder is 5μm.

[0062] S3. Weigh 30 parts of the modified polyester resin composition prepared in step S1, 10 parts of the modified conductive filler prepared in step S2, 30 parts of xylene, and 3 parts of leveling agent, respectively, by mass, and add the weighed modified polyester resin composition, modified conductive filler, cyclohexanone and leveling agent into a reactor, use an agitator and disperse them at a speed of 500 r / min. After dispersing for 2 hours, stir at a speed of 5000 r / min for 2 hours to obtain a coarse slurry of conductive ink.

[0063] S4. The obtained conductive ink coarse slurry is transferred to a grinder for grinding, and the roller spacing is adjusted to make the slurry fineness reach less than 20 um, and the material is filtered to obtain conductive ink powder.

[0064] S5. Adjust the viscosity of the obtained conductive ink powder to 12000 cps, stir it thoroughly, and mix it evenly to obtain conductive ink.

[0065] The prepared conductive ink was used as a silk-screen raw material, and the silk-screen piezoresistive sensing layer and a 5*6 array flexible pressure sensor were prepared in sequence by the same preparation method as in Example 1; and the area of ​​each sensing point on the prepared 5*6 array flexible pressure sensor was 1 cm 2 , the spacing between the sensing points is 8mm.

[0066] Comparative Example 1

[0067] A flexible pressure sensor was prepared, and the preparation steps were the same as those in Example 1, except that the polyester resin was directly used without preparing a modified polyester resin.

[0068] Comparative Example 2

[0069] A flexible pressure sensor was prepared, and the preparation steps were the same as those in Example 1, except that the conductive filler was directly used without modifying the conductive filler.

[0070] The performance tests were carried out on the flexible pressure sensors prepared in Examples 1-3 and Comparative Examples 1-2, including the minimum response force, force response range, differences in each sensing point, and piezoresistive stability. The test results are shown in Table 1.

[0071]

[0072] As shown in Table 1, compared with the flexible pressure sensor made in Comparative Example 1-2, the flexible pressure sensor made in Example 1-3 is a conductive ink prepared by using chemically modified saturated polyester resin, chemically modified conductive filler and other raw materials, and the conductive ink is used to make the sensing layer of the flexible pressure sensor and the flexible pressure sensor. The obtained flexible pressure sensor has a good minimum force response size, that is, it has a high sensitivity; and the flexible pressure sensor has a good response from the micro-force area to the large force area; at the same time, in the actual piezoresistive cycle test process, after 100,000 piezoresistive cycle tests, the flexible pressure sensor can also have a good piezoresistive stability, which further indicates that the flexible pressure sensor has good stability and a long life. It can be seen that through the synergistic effect between the components in the conductive ink, the flexible pressure sensor can have a high sensitivity to micro-pressure to large pressure, and has a sufficiently wide force response range and excellent piezoresistive stability; the flexible pressure sensor can identify the different degrees of expansion of the battery pack, and it can be better used in the field of energy storage to detect and warn the expansion force between battery packs.

[0073] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the scope of protection of the present invention. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims in the present invention.

Claims

1. A method for preparing a conductive ink, characterized in that: The following steps are involved: S1. Prepare a modified polyester resin composition for standby use; wherein the preparation steps of the modified polyester resin composition include: a. Weigh 100 parts of saturated polyester resin, 10-40 parts of xylene, and 10-30 parts of diisocyanate monomer respectively by mass, and add the weighed saturated polyester resin, xylene, and diisocyanate monomer into a reactor in sequence under nitrogen protection, then raise the temperature in the reactor from room temperature to 50-80° C., stir, so that the terminal hydroxyl group on the saturated polyester resin reacts with the isocyanate monomer, and after reacting for 0.5-1h, a polyester with an active group at the end is generated; b. Weigh 10-30 parts of an acrylic monomer with a hydroxyl group and 0.05-0.2 parts of dibutyltin diacetate respectively by mass, and add the weighed acrylic monomer with a hydroxyl group and dibutyltin diacetate to a reaction kettle in sequence, continue stirring, so that the polyester with an active group at the end and the acrylic ester monomer with a hydroxyl group undergo a cross-linking reaction, react for 1-4 hours, and then cool down to obtain a modified polyester resin composition; S2, using quaternary ammonium salt modified nanocellulose and conductive filler as raw materials to prepare modified conductive filler for standby use; S3, weighing the modified polyester resin composition prepared in step S1, the modified conductive filler prepared in step S2, the solvent, and the additives respectively according to proportion, and adding the weighed modified polyester resin composition, modified conductive filler, solvent, and additives into a reaction kettle, dispersing for 0.5-1h, and then stirring at a high speed for 1h-4h to obtain a conductive ink coarse slurry; S4, transferring the obtained conductive ink coarse slurry to a grinder for grinding, adjusting the roller spacing so that the slurry fineness does not exceed 20 μm, filtering the material to obtain conductive ink powder; S5. The viscosity of the obtained conductive ink powder is adjusted to within the range of 5000 cps-12000 cps, and the powder is fully stirred and mixed to obtain conductive ink.

2. The method for preparing a conductive ink according to claim 1, characterized in that: The diisocyanate monomer is any one or a combination of hexamethylene diisocyanate, isophorone diisocyanate, p-phenylene diisocyanate, and 1,4-cyclohexane diisocyanate; The acrylic monomer with hydroxyl group is any one of hydroxyethyl methacrylate, hexanediol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, and triethylene glycol dimethacrylate, or a combination of several of them.

3. The method for preparing a conductive ink according to claim 1, characterized in that: The steps of preparing the modified conductive filler include: i. Prepare a quaternary ammonium salt-modified nanocellulose dispersion with a mass percentage of 0.3%-3%; ii. Weigh the quaternary ammonium salt-modified nanocellulose dispersion and the conductive filler prepared in step i respectively according to proportion, and add the conductive filler to the quaternary ammonium salt-modified nanocellulose dispersion under stirring. Then, raise the temperature of the quaternary ammonium salt-modified nanocellulose dispersion from room temperature to 60° C.-90° C. to react. After reacting for 1 h-5 h, vacuum filtration, drying and grinding are performed to obtain a modified conductive filler.

4. The method for preparing a conductive ink according to claim 3, characterized in that: In the step ii, calculated by weight, the quaternary ammonium salt-modified nanocellulose dispersion is 100 parts, and the conductive filler is 30 parts.

5. An energy storage module according to claim 3, characterized in that: The conductive filler comprises carbon black and copper powder, and the weight ratio of carbon black to copper powder is 99:1-70:30; the average particle sizes of the carbon black and the copper powder are both 0.5-100 μm.

6. The method for preparing a conductive ink according to claim 3, characterized in that: The average particle size of the modified conductive filler is 0.3 μm-20 μm.

7. The method for preparing a conductive ink according to claim 1, characterized in that: In the step S3, the modified polyester resin composition is 10-30 parts, the modified conductive filler is 3-30 parts, the solvent is 5-40 parts, and the auxiliary agent is 0.5-3 parts, calculated by weight; The solvent is any one or more of DMF, NMP, cyclohexanone, dichloromethane and xylene; The auxiliary agent is any one or more combinations of leveling agents and defoaming agents.

8. A conductive ink, characterized in that: The preparation method is described in any one of claims 1 to 7.

9. A flexible pressure sensor, characterized in that: It includes two silk-screened electrode layers, two double-sided adhesive layers, and two silk-screened piezoresistive sensing layers; one silk-screened electrode layer and one silk-screened piezoresistive sensing layer are symmetrically bonded on both sides of each of the double-sided adhesive layers; the two silk-screened piezoresistive sensing layers are close to each other, so that the two double-sided adhesive layers are stacked up and down; The silk-screen piezoresistive sensing layer is prepared by using the conductive ink described in claim 8 as silk-screen raw material.

Citation Information

Cited By

  • Strain sensing and electric heating dual-function ink, preparation method thereof, device based on dual-function ink and application

    CN122483631A